Pemanfaatan Minyak Jelantah dalam Pengembangan Sabun Cair Ramah Lingkungan Melalui Substitusi Surfaktan Sintesis - Harefa, Meilinda Suriani; Try, Daniel; Siagian, Natalia; Simarmata, Gomoses Stevencus; Adha, Nabila Putri (Jurnal Pendidikan Ilmu Pengetahuan Alam (JP-IPA), 2025)
This study aims to develop an eco-friendly liquid soap made from used cooking oil through an experimental approach involving oil purification, saponification using KOH, pH adjustment with citric acid, and product quality testing. Information were collected through pH testing with litmus paper and organoleptic assessment of color, aroma, texture, and foam.  Data analysis was carried out descriptively, pH data was analyzed by observing three repetitions of measurements, while organoleptic data was analyzed by observing parameters to determine the level of subjectivity and quality of the soap. The results show that used cooking oil can be processed into liquid soap with a pleasant natural scent, clear green color, smooth texture, and good cleansing performance, with the pH successfully reduced from 12 to 7.5, making it safe for skin use. The product is feasible as an environmentally friendly alternative to synthetic surfactant-based soaps and supports sustainable waste utilization